2021
DOI: 10.6004/jnccn.2021.7062
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome Colorectal Cancer Puzzle: Initiator, Propagator, and Avenue for Treatment and Research

Abstract: The human gut microbiome has an ever-increasing role in the instigation and progression of colorectal cancer (CRC). Recent investigations have focused on identifying the key causative bacterial species and the composition and structure of the microbiome as a whole that ultimately lead to tumorigenesis in the colon. Understanding the bacterial mechanisms that promote CRC provides a rich area for the development of new screening modalities and therapeutics that may improve patient outcomes. This article reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The balance of microbes can undergo significant alterations resulting in major changes to the overall composition of the microbiome. This unfavorably altered composition is coined “dysbiosis” [ 8 , 9 ].…”
Section: Microbiome and Crc Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The balance of microbes can undergo significant alterations resulting in major changes to the overall composition of the microbiome. This unfavorably altered composition is coined “dysbiosis” [ 8 , 9 ].…”
Section: Microbiome and Crc Pathogenesismentioning
confidence: 99%
“…Biofilm formation represents a change in the epithelium-microbiome interaction. This change provides a resilient structure that decreases the penetration of antibiotics, increases epithelial permeability via loss of E-cadherin, and allows continued interaction between tumor-promoting bacteria and host cells [ 8 , 20 , 45 ]. This continued interaction at the level of unprotected epithelial cells promotes pro-carcinogenic tissue inflammation, inducing mutations within the epithelial cells, resulting in the increased proliferation seen with the growth of tumors [ 45 ].…”
Section: Microbiome and Crc Pathogenesismentioning
confidence: 99%
“…Increasing evidence points to the gut microbiome as a critical mediator of adenoma formation and CRC risk through parallel processes of co-metabolic dysfunction [11] , inflammation, epigenetic programming and DNA damage [12] . Multiple studies have identified the presence of intra-tumoural bacteria in precursors lesions of cancer [13] , [14] , [15] , [16] such as Fusobacterium nucleatum, Escherichia coli , and Bacteroides fragilis [17] . A loss of microbial diversity and increases in the abundance of both mucosal and faecal pathobionts can distinguish healthy persons from patients with CRC [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%